027 T2 mapping in acute and recovered myocarditis: potential role in clinical surveillance. (3rd April 2017) - Lota, AS; Wassall, R; Scott, AD; Gatehouse, PD; Wage, R; Smith, G; Tayal, U; Halliday, BP; Ware, JS; Firmin, D; Cook, SA; Cleland, JG; et al.
Abstract : Background: Acute myocarditis (AM) remains a challenging diagnosis with poorly defined markers of chronic active disease and/or progression to dilated cardiomyopathy. T2 mapping allows quantitative assessment of low- level myocardial oedema 1 but requires further clinical evaluation alongside conventional biomarkers (troponin and BNP) prior to large-scale application. 2 Aim: To prospectively evaluate the role of T2 mapping in the clinical surveillance of acute myocarditis. Methods: T2 mapping was performed using T2-prepared balanced steady-state free-single shot-images on a 3 Tesla system (Skyra, Siemens) in the following patient groups: Prospective patients with AM defined by clinical presentation and 2 out of 3 Lake Louise Criteria (n=11, mean age 34±10 years, all male) scanned at baseline and 3 months. Retrospective patients with a history of AM (n=12, mean age 35±13 years, all male) scanned 5.7±3.9 years from acute presentation. Healthy volunteers (n=9, mean age 27±6 years, 56% male). Troponin-I and BNP were measured at the time of CMR in all patients. A global region of interest was manually drawn by a single blinded observer in the basal short-axis slice (see figure 1 ). Results: In patients with acute myocarditis, mean global T2 was 42±1.4 msec compared to 40±1.3 msec in healthy volunteers (p<0.005). No difference was found between T2 values at presentation and 3 month follow-up (p=0.1), although the range of T2 values was greater at 3 months (see figure 2 ). In the retrospective group, mean T2 normalised to 40±1.5 msec with preserved ventricular function, comparable to healthy volunteers. Troponin normalised at follow-up in all patients, whereas BNP remained elevated in 3 patients (mean 23 ng/mL). Conclusion: Our findings suggest that T2 values remain persistently elevated at 3 months following acute presentation despite normalisation of cardiac troponin levels. Increased variability in T2 values at 3 months is likely to have arisen from heterogeneity in tissue changes, unlikely to be reflected by standard AHA segments. Statistical tools such as mean absolute standard deviation (madSD) 3 may improve the potential benefit of T2 mapping beyond single T2 cut-off values in this small but important subsets of patients. References: . Lurz P, Luecke C, Eitel I, et al. Comprehensive Cardiac Magnetic Resonance Imaging in Patients With Suspected Myocarditis: The MyoRacer-Trial. J Am Coll Cardiol2016;67(15):1800–11. . Heymans S, Eriksson U, Lehtonen J, et al . The Quest for New Approaches in Myocarditis and Inflammatory Cardiomyopathy. J Am Coll Cardiol2016;68(21):2348–64. . Baeßler B, Schaarschmidt F, Dick A, et al. Mapping tissue inhomogeneity in acute myocarditis: a novel analytical approach to quantitative myocardial oedema imaging by T2-mapping. J Cardiov Magn Reson2015;17(1):115.